(untitled) (Jurnal Bina Praja, 2023)
This study aims to explore the extent of Islamization in Bangladesh during the tenure of democratically elected leaders Sheikh Hasina and Khaleda Zia. The objective is to analyze the state of democratic governance in Bangladesh from a religious perspective, focusing specifically on Islamic political epistemology. It begins by defining Islamic Political Epistemology and its significance in acknowledging Islam’s role in democratic power. This qualitative descriptive analysis examines recent research papers from highly ranked resources such as Scopus. It is important to note that specific methods can strengthen strategies for enforcing electoral decrees, improve credentials for arbitration through sovereignty within the dominion branch, and increase national participation in political acts and society through Islamic Political Epistemology. Sheikh Hasina’s new regime has achieved significant progress in implementing Islamic development in bureaucracy and regulations. Qawmi Madrasah has contributed significantly to Islamic Education in Bangladesh, and the current government recognizes their educational certificates. The salaries of teachers and Imams at Government Madrasah-e-Alia have been increased, which is a significant policy change. The study revealed that Khaleda Zia’s government could have succeeded despite its alliance with Islamic political parties. Having a coalition with Islamic political parties does not necessarily mean that the country’s political ideology is institutionalized in an Islamic way. Opposite, Bangladesh’s government, with partial financing from Saudi Arabia, is constructing 560 mosques that will also serve as artistic centres to promote Islamic epistemology and combat extremism. However, this government operates under a one-party system with the Awami League party, led by Sheikh Hasina, idolizing Sheikh Mujibur Rahman.